The Level of Professional Belonging and Its Influencing Factors - A Field Study on a Sample of Career Guidance Advisors at the Directorate of Education in Laghouat - Miada BENKOUIDER; Mohamed SAKHRI (Social Sciences Journal, 1970)
The study aims to determine the level of professional belonging among guidance and career counseling advisors at the Directorate of Education in the city of Laghouat, and to reveal differences in the level of belonging between school and career guidance advisors according to the variables of professional seniority and educational qualification.The research adopted a descriptive method, using a comprehensive survey of all school and career guidance advisors in Laghouat, totaling 83 advisors, which allowed for the collection of comprehensive data on their level of professional belonging. A questionnaire designed by the researchers was used for data collection.The results showed that the advisors’ level of professional belonging is generally high, reflecting a positive work environment that provides a sense of integration and appreciation. The study also revealed differences according to educational qualification, with those holding a Bachelor’s or Master’s degree showing greater professional belonging than those holding a Doctorate. Furthermore, the findings indicated that professional seniority positively influences the level of belonging, as more experienced advisors demonstrated stronger attachment compared with newcomers.